2020
DOI: 10.1111/jors.12511
|View full text |Cite
|
Sign up to set email alerts
|

Coming to stay or to go? Stay intention and involved uncertainty of international students

Abstract: Countries compete for young talents to alleviate skilled-labor shortage. International students, who stay after graduation, allow host countries to overcome those challenges. This study investigates the factors associated with international students' intention to stay or to go after graduation. In contrast to the existing literature, this analysis employs survey data collected at the beginning of the studies. This assures that the analysis is not distorted by attrition and provides policymakers with more time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…They typically return to their countries of origin with a positive impact on economic and technological development (Abodohoui & Su, 2020; Le, 2010). However, there are also many who decide to stay in their host countries after graduation as an important means of alleviating the labour shortage in such countries (Koenings et al, 2021; Tung & Lazarova, 2006). In fact, aside from staying and returning, more students are torn between options with no clear direction (Koenings et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They typically return to their countries of origin with a positive impact on economic and technological development (Abodohoui & Su, 2020; Le, 2010). However, there are also many who decide to stay in their host countries after graduation as an important means of alleviating the labour shortage in such countries (Koenings et al, 2021; Tung & Lazarova, 2006). In fact, aside from staying and returning, more students are torn between options with no clear direction (Koenings et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The motivational elements may change at different stages of students' experiences, leaving the perspective open to a high degree of uncertainty (Koenings et al, 2021;Suryani et al, 2018).…”
Section: Stage 3: Outcomes After Studying Abroadmentioning
confidence: 99%
“…International graduates from German universities can help alleviate the shortage of skilled specialists in Germany. For this reason it makes sense to look at how many international students want to stay in Germany and how integration in the labour market can be ensured (for previous studies on the topic, see Forschungsbereich beim Sachverständigenrat deutscher Stiftungen für Integration und Migration, 2017; Hanganu, 2015;Hanganu & Heß, 2014;Koenings et al, 2021;Morris-Lange, 2019). Participants in the International Student Survey who indicated that they had completed their studies were asked about their future plans (see Fig.…”
Section: Plans After Graduationmentioning
confidence: 99%
“…28). In general, previous studies show that at least half of the students already plan to stay in Germany when they start their studies ( Koenings et al, 2021;Thies, forthcoming).…”
Section: Plans After Graduationmentioning
confidence: 99%
“…Internationale Absolventinnen und Absolventen deutscher Hochschulen können dazu beitragen, den Fachkräftemangel in Deutschland zu lindern. Daher ist es relevant zu erforschen, wie viele internationale Studierende in Deutschland bleiben wollen und wie eine Integration in den Arbeitsmarkt gewährleistet werden kann (für bisherige Studien zum Thema, siehe Hanganu, 2015;Hanganu & Heß, 2014;Koenings et al, 2021;SVR-Forschungsbereich, 2017;Morris-Lange, 2019). Teilnehmerinnen und Teilnehmer des International Student Survey, die einen Studienabschluss angaben, wurden nach ihren Zukunftsplänen gefragt (siehe Abb.…”
Section: Pläne Nach Dem Studienabschlussunclassified